PREM KUMAR ATTEMPTS IN MAINTAINING BOURGEOIS STATUS QUO AS REFLECTED IN VIKAS SWARUP’S “Q AND A” NOVEL - FIRDIANSYAH, ANDREW RIZKY (Jurnal Ilmiah Mahasiswa FIB, 2014)
Firdiansyah, Andrew. 2013.  Prem Kumar Attempts in Maintaining Bourgeois Status Quo as Reflected in Vikas Swarup’s “Q and A” Novel. Study Program of English, Department of Language and Literature,  Faculty of Cultural Studies, Universitas Brawijaya. Supervisor: Sugeng Susilo Adi; Co-supervisor: Scarletina Vidayayani Eka.Keywords: Capitalism, Bourgeois, Status Quo, Modern Capitalism, Bourgeois ProletariatCapitalism has become the basic of economic systems in the modern era. Money determines  someone’s status and position in the  society. In capitalist systems, group or individual who has money is called bourgeois class, and the one that are not is called the proletariat. To get surplus value and maintain its present state, the Bourgeois class has going to do any effort needed, whether it is legal or illegal. This research aims to ensure the bourgeois’ effort to maintain their status quo in Q and A novel (2005). Marxist Approach is used because the efforts of the Bourgeois in the novel Q and A are representation the act of maintaining the status quo and  the act to  get a surplus value. The researcher analyzes the Bourgeois efforts in maintaining the status quo and how they do that. Based on the data collected from novel, the researcher finds a lot of evidence concerning the Bourgeois efforts to maintain the status quo in the characters behavior in the novel. The efforts taken by the Bourgeois includes using money as a bait and giving fake hope on the Lumpen Proletariat, and also deceiving the Proletariat with the wrong clues,  then abusing them mentally and physically which are done by the help of the police.